Serum protein levels following surgery in breast cancer patients: A protein microarray approach - Pérez-Rivas, Luis G.; Jérez, J.M.; Fernández-De Sousa, C.E.; De Luque, Vanessa; Quero, C.; Pajares, Bella; Franco, L.; Sánchez-Muñoz, Alfonso; Ribelles, Nuria; Alba-Conejo, Emilio (Spandidos Publications, 2012)
Surgery is the primary treatment for non-metastatic breast cancer. However, the risk of early recurrence remains after surgical removal of the primary tumor. Recurrence is suggested to result from hidden micrometastatic foci, which are triggered to escape from dormancy by surgical resection of the primary tumor. In this study, we focused on the differential impact of breast surgery on the serum profiles of early breast cancer patients and healthy women. Serum samples from invasive breast cancer patients, in situ carcinoma breast cancer patients and healthy women were analyzed using reverse phase protein array technology. Samples were collected prior to breast surgery and 24 h following breast surgery. Both the expression level and the velocity of 42 serum proteins were quantified and compared among groups. We found that surgery increased the concentration of several proteins (CSF1, THSB2, IL6, IL7, IL16, FasL and VEGF-B) in the overall population. Compared with healthy women and patients with non-invasive tumors, invasive tumor patients exhibited higher preoperative levels of several serum proteins, such as αFP, IFNβ1, VEGF-A, IL18, E-cadherin or CD31, and lower postoperative levels of TNFα and IL5. Similarly, we detected significant surgery-induced changes in the velocity of VEGF-A and IL16 accumulation in samples derived from invasive breast cancer patients. In conclusion, breast surgery induced distinct changes in the concentrations and dynamics of serum proteins in invasive breast cancer patients compared with healthy women and noninvasive tumor patients.
Este artículo ha sido publicado en INTERNATIONAL JOURNAL OF ONCOLOGY No hemos podido encontrar infomración sobre si permite depositar conlicencia creative Commons El archivo solicitado a la editorial como postprint que nos ha remitido es el que depositamos
Keywords: Mamas - Cáncer - Investigación; breast cancer; surgery; reverse phase protein array; serum protein profile; dormancy